Kajian Literatur Sistematik Tentang Program Parenting untuk Food literacy bagi Anak Usia Dini - Ningsih, Viro Yunarti; Mustapa, Noviana; Patilima, Hamid; Syarah, Erie Siti (UIN Sultan Maulana Hasanudin Banten, 2025)
Low parental nutrition literacy is one of the contributing factors to the suboptimal development of healthy eating habits among young children in Indonesia. This study aims to identify and systematically analyze the forms of parenting program interventions that enhance food literacy among parents and support the development of healthy eating behaviors in early childhood. A Systematic Literature Review (SLR) was conducted on scientific articles published between 2014 and 2024. A total of 8 articles that met the inclusion criteria were analyzed narratively. The findings reveal that effective parenting programs integrate educational, participatory, and contextual approaches, including practical skill training, hands-on activities, and community-based education. Key indicators of success include improved parental nutrition literacy, responsive feeding practices, and increased consumption of healthy food among children. The review also highlights several research gaps, such as the limited number of longitudinal studies and the lack of integration between food literacy and health promotion. These findings imply the need to develop more structured and sustainable parenting programs rooted in local cultural contexts.